Financial Accounting as a Tool to Enhance Non-Government Organisations’ Performance: A Case Study of a Large NGO in Durban, South Africa - Mvunabandi, Jean Damascene; Lathleiff, Charmaine; Muzindutsi, Paul-Francois (International Journal of Economics and Financial Issues, 2022)
Numerous non-governmental organisations (NGOs) in South Africa and elsewhere do not have standardised financial accounting practices to follow in preparing their financial statements and it is not clear whether the International Financial Reporting Standards (IFRS) for Small and Medium-sized Entities (SMEs) can be used to enhance NGOs performance (Kaya et al., 2015). This article explored the applicability of financial accounting practices as a relevant tool to enhance NGO performance with particular reference to a large NGO in Durban, South Africa. A qualitative approach was employed and data was collected through the use of semi-structured interviews and conventional thematic and document analysis. Evidence from this study showed that despite adopting accounting and financial policy and procedures, the selected NGO finds it difficult to maximise its financial performance due to failure to fully comply with IFRS for SMEs in South Africa. This article provides necessary recommendations applicable to other similar NGOs globally.